Figurative Language Found In Harry Styles’ Song Lyrics - I Kadek Risky Yusadana Putra; Ida Bagus Gde Nova Winarta (University of Darussalam Gontor, 2022)
Figurative language is a language that conveys thoughts or feelings in different forms to obtain effects and to emphasize certain meanings. This study describes the analysis of figurative language in Harry Styles’ song lyrics. The purpose of this study was 1) to determine the type of figurative language in Harry Styles’ songs using the theory of Knickerbocker & Reninger (1963) and 2) to explain the meaning of the figurative language contained in it (Leech, 1981). The data sources were obtained from 10 Harry Styles songs that have the highest number of viewers on their YouTube channel. This research used the descriptive qualitative method to analyze data and the observation method in collecting research data. From the results of the analysis, there are ten types of figurative language in thirty-four sentences of the data. They are simile (1 sentence, 2.94%), metaphor (5 sentences, 14.70%), personification (5 sentences, 14.70%), synecdoche (1 sentence, 2.94%), metonymy (3 sentences, 8.82%, hyperbole (14 sentences, 41.18%), irony (2 sentences, 5.90%), paradox (1 sentence, 2.94%), dead metaphor (1 sentence, 2.94%), and allusion (1 sentence, 2.94%)